Hypokalemic paralysis and renal tubular acidosis: Initial presentation of Sjogren’s syndrome - Tofail, Tania; Jahan, Sharmin; Hasnat, Mohd Abul (Bangladesh Journal of Medicine, 2021)
Sjogren’s syndrome is a rare autoimmune disease affecting multiple systems with varying clinical features.We report a case of 37 year old woman who presented with recurrent episodes of quadriparesis which was attributable to hypokalemia and initially labelled as hypokalemic periodic paralysis. Later on she was found to have metabolic acidosis rather than alkalosis which pointed towards the diagnosis of renal tubular acidosis (RTA) in the absence of apparent gastrointestinal tract loss. Once the diagnosis of RTA was established, an attempt to search the aetiology revealed that she was having primary Sjogren’s syndrome (pSS) though she did not have any symptom at the time of diagnosis. She was found positive for anti-SSA. Lip biopsy revealed lymphocytic infiltration in periductal as well as parenchymal region. Schirmer test confirmed presence of severe dry eye. A concomitant existence of autoimmune hypothyroidism was a noteworthy association. She responded well with potassium supplementation and symptomatic treatment. Presentation of this case reminds the importance of vigilance while managing a case of recurrent hypokalemia which might be a rare presenting feature of pSS. Bangladesh J Medicine July 2021; 32(2) : 145-148